English linguistic purism: history, development, criticism - Grishechko Ovsanna Savvichna; Akopova Asya Savvichna; Grishechko Elizaveta Georgievna (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2015)
Linguistic purism as an area of linguistic analysis describes the practices of identification and acknowledgement of a certain language variety as more structurally advanced as compared to its other varieties. Linguistic protection is associated with preservation of some abstract, classical, conservative linguistic ideal and performs the regulatory function, above all. The puristic approach to the development of the English language has been subjected to heated debate for several centuries and is reflected in both scientific research and literary texts. Supporters of purification of the English language champion the idea of protection of “pure language”. The idea, however, is actively criticized by opponents.